2007
DOI: 10.1080/02770900601180313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Asthma and Gestational Asthma Therapy on Fetal Growth

Abstract: Asthma is a common chronic condition that might seriously complicate pregnancy and fetal development. This article provides a comprehensive review of the existing literature regarding the effect on fetal growth of maternal asthma and common asthma medications used during pregnancy, including short-and long-acting beta (2)-agonists, inhaled and oral corticosteroids, chromones, leukotriene receptor agonists, and theophylline. Evaluated outcomes of fetal growth include low birth weight, mean birth weight, small f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…6 Slightly decreased birth weight in infants born to women who used LTRAs in our study is most likely attributable to more severe and/or poorly controlled maternal asthma in that group. Maternal asthma has been associated with an increased risk of low birth weight, [26][27][28][29] reduced mean birth weight, 28,30 and intrauterine growth restriction 6,26,31,32 (reviewed by Bakhireva et al 22 ). Moreover, relationships have been reported between reduced intrauterine growth and more severe or poorly controlled asthma, as defined by lower pulmonary function, 5 increased symptoms, 6 or exacerbations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6 Slightly decreased birth weight in infants born to women who used LTRAs in our study is most likely attributable to more severe and/or poorly controlled maternal asthma in that group. Maternal asthma has been associated with an increased risk of low birth weight, [26][27][28][29] reduced mean birth weight, 28,30 and intrauterine growth restriction 6,26,31,32 (reviewed by Bakhireva et al 22 ). Moreover, relationships have been reported between reduced intrauterine growth and more severe or poorly controlled asthma, as defined by lower pulmonary function, 5 increased symptoms, 6 or exacerbations.…”
Section: Discussionmentioning
confidence: 97%
“…Gestational age-specific and sex-specific percentiles for birth weight, height, and head circumference were defined as small for gestational age if they were 10th percentile. 22 Ponderal index was evaluated as a measure of asymmetrical intrauterine growth restriction, 23 calculated as birth weight (g)/birth length (cm) 3 , and dichotomized as normal (2.2) or low (<2.2). Preterm delivery was defined as < 37 completed weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…There was a modest risk for miscarriage. Baibergenova et al [26] also reported no adverse effects in pregnancy among the 530 women with asthma who were studied, while Bakhireva et al [27 ] found no or minimal effect of asthma medicines on fetal growth for pregnant women with asthma and that perinatal complications were reduced among women with well managed disease.…”
Section: Asthma In Pregnancymentioning
confidence: 94%
“…Previous studies found increased risks for birth defects and other adverse pregnancy outcomes including oral clefts, spontaneous abortion or stillbirth, preterm delivery, preeclampsia, low birth weight, neonatal hypoxia, and cesarean section (4-6). Previous studies are based on pregnancy registries, birth defects surveillance programs, observational cohort studies, and case-control studies.…”
Section: Introductionmentioning
confidence: 99%